STUDY ON THE NEW PROCESS DEVELOPMENT OF TREATED DISTILLATE AROMATIC EXTRACT PRODUCTION BY - Priscilla Sinaga, Ribka
Distillate Aromatic Extract (DAE) is a derivative of petroleum products with high aromatic content. DAE is utilized by rubber industry as plasticizer oil, especially in tire manufacturers. DAE is a byproduct of the solvent extraction process for vacuum distillates in FEU (Furfural Extraction Unit) for lubricating oil production. Treated Distillate Aromatic Extract (TDAE) is obtained from Distillate Aromatic Extract (DAE) feed in an extended extraction process to meet PCA (Polycyclic Aromatic) content of less than 3% by weight and suitable for use as RPO (rubber processing oil) in the tire compound manufacturing industry. In addition to PCA levels, high selling value TDAE products shall have kinematic viscosity in the range of 17 - 22 cSt when measured at 100oC. The purpose of this research is to evaluate the potential of FEU (Furfural Extraction Unit) if it will be used as the unit for the new extraction-based TDAE production process without using a diluent. It is also expected through this research that the reduction of PCA level in the DAE feed could be proved through a shake flash extraction method by manipulating proper process variables, such as variations in the mixed feed components of DAE, the ratio of furfural solvent to feed DAE, and the number of extraction tahap. This study uses Aspen HYSYS process simulation software as a tool to obtain an overview regarding the feasibility of the TDAE production process technology without using diluent and uses real feed specifications from Refinery Unit IV Cilacap. Through this research, it is proved that the IDIS component can be used as a diluent to replace the role of the diluent (n-hexane). Eight variations of experiments carried out in the laboratory (shake extraction test) succeeded in reducing the PCA content by more than 50% and meet the specifications for the aromatic content of at least 25%. In line 2, the best PCA content value is 3.6%. In this research, a simulation model of TDAE production was created referring to the operating conditions of the SPO mode and validated with the actual data of the Pertamina Refinery Unit IV Daily Monitoring. The simulation model that was built was able to show that the level of NPCA and Oil extraction in the shake extraction test experiment was too large which could possibly caused by incomplete iv separation of the extract phase and the raffinate phase by precipitation in the shake extraction test experiment. If the extraction process is carried out on an extraction tool that has more reliable performance, such as the operating unit in the field, namely the FEU Unit (Furfural Extraction Unit) which uses an RDC (Rotating Disc Contactor) unit which is then added with a Settler vessel operating at a lower temperature, the achievement of the TDAE yield value and the total aromatic content in the TDAE product from DAE extraction without the use of diluents can be expected to be close to the ideal value. The increase in extraction efficiency at the SFR (Solvent to Feed Ratio) value will continue to increase the yield and PCA content in TDAE products because fewer portions of raffinate are trapped and staycarried in the extract phase. Similarly, if the SFR is increased at a constant extraction efficiency, the yield and PCA content in the TDAE product will decrease as more oil components and less selective NPCA are extracted with PCA. The results of this logical prediction indicate that the simulation model has good validity. This process model consistently describes the impact of the raffinate phase in the extract phase due to the possibility of imperfect mixing and precipitation in batch extraction experiments. Keyword: DAE, TDAE, furfural, without diluent, Furfural Extraction Unit, Aspen HYSYS